Menumbuhkan Kemampuan Berpikir Kreatif Peserta Didik SMP Melalui Perangkat Pembelajaran Berbasis Teori M-APOS - Suske, Ihksan Apria; Yerizon, Yerizon; Armiati, Armiati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The ability to think creatively is an ability that is expected to be mastered by students but is still low. Students lack the ability to solve a problem in a various ways.The purpose of this study is to produce a learning tool based on M-APOS theory to improve students' creative thinking abilities.The research method used in this research is research and development which consists of three stages, namely the initial investigation stage, the development stage and the assessment stage.In this section what is done is the preliminary research stage. The instruments used were interview and questionnaire guidelines.The results of the study are: 1) inadequate school facilities and infrastructure, 2) student learning outcomes are still low because students are accustomed to accept what is taught and do not repeat the lessons at home, 3) worksheets that are used by students is not attractive, 4) in the learning process students prefer group learning, 5) students want the questions contained in LKPD to be daily life problems, 6) the learning environment of students who are in the hills and close to the highway, 7) learning styles favored by students are in the form of solving problems in the form of images related to daily life problems, 8) the appearance of worksheets that are liked by students is LKPD which has  pictures and attractive color.